2005
DOI: 10.1074/jbc.m411147200
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin-dependent E1A Activity Modulates NF-κB RelA-mediated Repression of Glucocorticoid Receptor-dependent Transcription

Abstract: The role of chromatin-dependent regulatory mechanisms in the repression of glucocorticoid-dependent transcription from the murine mammary tumor virus (MMTV) promoter by p65 and E1A was investigated by using chromatin and transiently transfected reporters. The p65 RelA subunit of NF-B represses MMTV expression on either transient or integrated reporters. In contrast, the viral oncoprotein E1A represses a transient but not an integrated MMTV. E1A repression is attenuated by chromatin, suggesting p65 but not E1A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 71 publications
1
17
0
Order By: Relevance
“…7 Thus, it is conceivable that in on hand the binding of RelA to the bax gene promoter might directly block p73 and RNA pol II recruitment through a mechanism of steric hindrance, as observed for RelAmediated repression of glucocorticoid-receptor-dependent transcription. 31 In another hand, RelA may repress p73-mediated transcription by both sequestering the coactivator p300/CBP and favoring the recruitment of corepressor HDAC complexes (Figure 6d), as observed in other systems. 20,21 CD28 is an important regulator of T-cell survival by inducing the expression of antiapoptotic proteins, in particular of Bcl-xL.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…7 Thus, it is conceivable that in on hand the binding of RelA to the bax gene promoter might directly block p73 and RNA pol II recruitment through a mechanism of steric hindrance, as observed for RelAmediated repression of glucocorticoid-receptor-dependent transcription. 31 In another hand, RelA may repress p73-mediated transcription by both sequestering the coactivator p300/CBP and favoring the recruitment of corepressor HDAC complexes (Figure 6d), as observed in other systems. 20,21 CD28 is an important regulator of T-cell survival by inducing the expression of antiapoptotic proteins, in particular of Bcl-xL.…”
Section: Discussionsupporting
confidence: 55%
“…Basu et al 34 have recently reported that Akt phosphorylates the Yes-associated protein (YAP), thus impairing its nuclear translocation and inhibiting its function as strong transcriptional coactivator of p73. 35 Thus, CD28-mediated activation of Akt may lead to both the inactivation of YAP and the recruitment of RelA-containing repressor complexes 31 on the bax gene promoter (Figure 7c), thereby completely blocking p73-mediated transcriptional activity.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we described BRG1 as a co-repressor of ZEB1. Although BRG1 is better known for its role in promoting transcriptional activation-via nuclear receptors, MEF2D, Smad3, STAT1/2-it also participates in gene silencing through its direct interaction with transcriptional repressors (Zhang et al, 2000;Burkhart et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence has shown that RelA-mediated repression of an integrated GRE-driven MMTV promoter construct requires the brahma-related gene 1 (Brg1) chromatin-remodeling activity (Burkhart et al, 2005;Chen et al, 2006). Reciprocally, differential NF-kB target gene expression was recently found to rely on different (antagonistic) functions of the chromatinremodeling complexes Brg1, Brm, Mi-2b (nucleosome remodeling and histone deacetylase (NuRD)) (RamirezCarrozzi et al, 2006;Vanden Berghe et al, 2006b).…”
Section: Novel Prospects and Research Areasmentioning
confidence: 99%
“…For example, much attention now focuses on learning how to read and interpret the 'histone code', inferring an additional level of dynamic gene regulation. Chromatin organization plays a major role in controlling the dynamic nature of NF-kB recruitment to target genes and represents an integration point for mediating diverse interactions between TFs (Burkhart et al, 2005;Natoli et al, 2005;Natoli and De Santa, 2006;Vanden Berghe et al, 2006b). This information is paramount for researchers interested in mechanisms of hormonal repression of NF-kB-driven gene expression, as additional key regulators of this process are still emerging.…”
Section: Introductionmentioning
confidence: 99%